2011
DOI: 10.1016/j.stem.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Copy Number of Pluripotency and Cell Proliferation Genes in Human ESCs and iPSCs during Reprogramming and Time in Culture

Abstract: Genomic stability is critical for the clinical use of human embryonic and induced pluripotent stem cells. We performed high resolution SNP (single nucleotide polymorphism) analysis on 186 pluripotent and 119 non-pluripotent samples. We report a higher frequency of subchromosomal copy number variations in pluripotent samples compared to non-pluripotent samples, with variations enriched in specific genomic regions. The distribution of these variations differed between hESCs and hiPSCs, characterized by large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
699
11
18

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 817 publications
(767 citation statements)
references
References 31 publications
30
699
11
18
Order By: Relevance
“…Another study focused on copy number variation (CNV) (approximately 0.6-12,000 kb stretches of genomic DNA) of a large number of pluripotent and somatic samples. iPSC had on average 17 CNV per sample [70]. As a comparison ESC also had 17 and nonpluripotent samples had 12 CNV.…”
Section: Mutational Load Of Ipscmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study focused on copy number variation (CNV) (approximately 0.6-12,000 kb stretches of genomic DNA) of a large number of pluripotent and somatic samples. iPSC had on average 17 CNV per sample [70]. As a comparison ESC also had 17 and nonpluripotent samples had 12 CNV.…”
Section: Mutational Load Of Ipscmentioning
confidence: 95%
“…Besides epigenetic aberrations it is reported that iPSC also bear genomic mutations [69][70][71][72]. These could arise from the reprogramming itself and from the in vitro expansion of cells afterward.…”
Section: Mutational Load Of Ipscmentioning
confidence: 99%
“…A series of recent articles suggest that iPSCs display more abnormalities than do ESCs and fibroblasts. Chromosomal abnormalities seem to appear earlier in iPSCs cultures, 70 and higher frequency of mutations and greater number of novel copy number variants are also present in iPSCs. 70,71 Aberrant DNA methylation and retention of epigenetic markers from the cell of origin also suggest significant reprogramming variability in human iPSCs.…”
Section: From Embryonic Stem Cells To Germ Cellsmentioning
confidence: 97%
“…Chromosomal abnormalities seem to appear earlier in iPSCs cultures, 70 and higher frequency of mutations and greater number of novel copy number variants are also present in iPSCs. 70,71 Aberrant DNA methylation and retention of epigenetic markers from the cell of origin also suggest significant reprogramming variability in human iPSCs. 72 As it stands, the lack of genetic stability in iPSCs precludes their use in clinical applications in humans until further research defines the effect of this recent finding.…”
Section: From Embryonic Stem Cells To Germ Cellsmentioning
confidence: 97%
“…[52][53][54] The same is true for the facts, that the epigenetic memory of the original differentiated state is not perfectly erased during reprogramming 55,56 and that iPS cells have been reported to accumulate karyotypic abnormalities and gene mutations during propagation in culture. [57][58][59][60] AFS very likely do not harbour accumulated somatic mutations, because they are primary cells of a very early stage of human development. Furthermore, monoclonal human AFS cell lines have been reported to maintain genome stability during expansion and do not induce tumour formation in severe combined immunodeficient mice.…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 99%